Sistem Pendukung Keputusan Penerimaan Mitra Waralaba OMI Pada PT Inti Cakrawala Citra (Indogrosir) Medan Menggunakan Metode Navie Bayes - Armansyah Ritonga; Nelly Astuti Hasibuan; Edward Robinson Siagian; Fince Tinus Waruwu; Muhammad Syahrizal (JURIKOM (Jurnal Riset Komputer), 2021)
In accordance with the vision of Indogrosir who wants to become a National Asset, since September 2001, Indogrosir has also introduced a modern minimarket franchise system under the name OMI (Outlet Partner of Indogrosir). Indogrosir cooperates with government and private cooperatives, MSMEs, gas stations or general entrepreneurs who want to develop their business in the form of modern minimarkets. Decision support system is a computer-based system that helps in making decisions to solve unstructured problems. The Naive Bayes method is a probabilistic classification technique based on the Bayes theorem which uses the assumption of attribute independence (there is no link between attributes) in the classification process. In an easy rule, a Naive Bayes classification is assumed that the presence or absence of certain features of a class has nothing to do with the characteristics of other classes. With the existence of this decision support system, it is expected to facilitate decision making in determining the recipient of new partners where policies and decisions are made based on predetermined criteria